The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1177/039463201102400414
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-23, VEGF and TLR2/TLR4 on Mononuclear Cells after Exposure to Pseudomonas Aeruginosa

Abstract: Pseudomonas aeruginosa is a Gram-negative, aerobic bacillus causing infections of the respiratory and other organ systems in susceptible hosts. Although it does not cause pulmonary infections in immunocompetent individuals, P. aeruginosa causes chronic lung infection in individuals with cystic fibrosis and nosocomial pneumonia resulting in significant morbidity and mortality. Exogenous administration of an important P. aeruginosa virulence factor, lipase, present in P. aeruginosa culture supernatant, induces p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Furthermore, Tang et al noted that activation of Toll‐like receptor‐4 (TLR4) signalling by blood‐borne gram‐negative bacteria led to greater CCM lesion burden in a mouse model of CCM . In addition to activation of TLR4, infection with gram‐negative bacteria can be associated with increased expression of VEGF . Our data are consistent with these observations.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, Tang et al noted that activation of Toll‐like receptor‐4 (TLR4) signalling by blood‐borne gram‐negative bacteria led to greater CCM lesion burden in a mouse model of CCM . In addition to activation of TLR4, infection with gram‐negative bacteria can be associated with increased expression of VEGF . Our data are consistent with these observations.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it has been reported that P. aeruginosa infection is associated to stimulation of TLR4 receptors, leading to an activation of the NF-κB pathway [49]. To assess the impact of inulin and FOS on the inflammatory response, the role of the NF-κB and MAPK signalling pathways in the FOS-mediated modulation of macrophages was assessed.…”
Section: Resultsmentioning
confidence: 99%
“…21 After BS-14 stimulation, TLR2 was mainly expressed on precursor B cells at 72 h. Some of the bacteria contained in BS-14 can induce TLR2, such as Klebsiella pneumonia and Pseudomonas sp. 16,[22][23][24] Remarkably, it has been reported that some TLR2 ligands induce IL-10, thereby leading to activation of regulatory B cells and the attenuation of T effector functions, which contribute to immune regulation. 25 It is possible that BS-14 stimulation functionally expands a subgroup of Bregs characterized by TLR2 expression and IL-10 production.…”
Section: Discussionmentioning
confidence: 99%